2017
DOI: 10.3899/jrheum.170044
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Serological Gap in the Antiphospholipid Syndrome: The Value of “Non-criteria” Antiphospholipid Antibodies

Abstract: Objective.Most clinicians use the 2006 Sydney classification criteria to evaluate patients suspected of having antiphospholipid syndrome (APS). Although sensitive and specific for APS, many patients fulfilling clinical criteria for the syndrome are persistently negative for the specific serological tests (“laboratory criteria”). These “seronegative APS” (SN-APS) patients can go undiagnosed and untreated until they experience serious clinical events. This study’s objective was to describe antibody profiles of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 33 publications
(36 reference statements)
1
53
1
1
Order By: Relevance
“…As to the relationship between aPLs and clinical manifestations, all of the biomarkers explored here are better predictors of late pregnancy morbidity rather than early pregnancy morbidity, supporting the concept that late pregnancy morbidity is a more specific clinical manifestation of the disease. Our results showed a higher prevalence of non-criteria aPL compared with similar studies previously reported [38,40,41]. On the one hand, variability between commercial diagnostic kits and lack of standardization among laboratories may account for the discrepancy.…”
Section: Discussionsupporting
confidence: 66%
“…As to the relationship between aPLs and clinical manifestations, all of the biomarkers explored here are better predictors of late pregnancy morbidity rather than early pregnancy morbidity, supporting the concept that late pregnancy morbidity is a more specific clinical manifestation of the disease. Our results showed a higher prevalence of non-criteria aPL compared with similar studies previously reported [38,40,41]. On the one hand, variability between commercial diagnostic kits and lack of standardization among laboratories may account for the discrepancy.…”
Section: Discussionsupporting
confidence: 66%
“…The Authors found that one-third of the 'seronegative' sera gave positive results. 24 The study concluded that patients with clinical features of APS, but negative for conventional criteria markers, should undergo additional testing for non-criteria biomarkers. 24 A recent study evidenced that positivity for the extracriteria aPL was <1% in SN-APS (thrombotic or obstetric); however, the lack of clear inclusion and exclusion criteria does not allow a precise estimation of the prevalence to be made.…”
Section: Study Typology Population Apl Positivity In Sn-aps (N) Main mentioning
confidence: 99%
“…24 The study concluded that patients with clinical features of APS, but negative for conventional criteria markers, should undergo additional testing for non-criteria biomarkers. 24 A recent study evidenced that positivity for the extracriteria aPL was <1% in SN-APS (thrombotic or obstetric); however, the lack of clear inclusion and exclusion criteria does not allow a precise estimation of the prevalence to be made. 25 Similarly, non-criteria antibodies were detected in 18.8% of SN-APS patients also in a Chinese cohort composed of APS and patients with only clinical criteria for APS.…”
Section: Study Typology Population Apl Positivity In Sn-aps (N) Main mentioning
confidence: 99%
“…Several authors have suggested that the assessment of new autoantibodies can help to identify the syndrome in patients with APS clinic (7)(8)(9)(10). Among the new aPL that have been described associated with APS-events, the IgA aB2GP1 and the anti-phosphatidyl serine/prothrombin (IgG or IgM) are those where a greater association with the APS clinical aspects has been observed (11)(12)(13).…”
mentioning
confidence: 99%